The framingham risk score, diet, and inflammatory markers in Korean men with metabolic syndrome - Sohn, C.M., Wonkwang University, Iksan, Republic of Korea; Kim, J.Y., Health Promotion Center, Seoul National University of Bundang Hospital, Seongnam, Republic of Korea; Bae, W.K., Health Promotion Center, Seoul National University of Bundang Hospital, Seongnam, Republic of Korea (Nutrition research and practice, 2012)
The Framingham risk score (FRS) has been used to assess the risk of a cardiovascular event and to identify patients for risk factor modifications. Therefore, the purpose of this study was to evaluate the relationship of the FRS with dietary intake and inflammatory biomarkers. We conducted a cross-sectional study of 180 men (49.2 ± 10.2 years) with MS. Serum levels of high sensitive C-reactive protein (hs-CRP), interleukin-6 (IL-6), and adiponectin were examined. Participants were asked to complete the food frequency questionnaire (FFQ) using the previous 1 year as a reference point. The absolute cardiovascular disease (CVD) risk percentage over 10 years was calculated to estimate the FRS, which was classified as low risk (less than 10%), intermediate risk (10-20%), and high risk (greater than 20%). Mean intake of polyunsaturated fatty acids was lower in subjects who had greater than 20% FRS than in subjects who had less than 10% FRS (3.7 ± 1.9 g/day vs. 4.7 ± 1.9 g/day; P less than 0.05). Significant differences in the Index of Nutritional Quality of protein, phosphorus, iron, vitamin A, vitamin B-1, niacin, vitamin B-6, and vitamin C were observed between the greater than 20% FRS group and the less than 10% FRS group (P less than 0.05). IL-6 concentrations were significantly lower in subjects with a less than 10% FRS than in subjects who were 10-20% FRS or greater than 20% FRS (0.91 ± 0.26 vs. 1.48 ± 033 vs. 2.72 ± 0.57 pg/mL, respectively; P less than 0.05). IL-6 and dietary intake of polyunsaturated fatty acids together explained 6.6% of the variation in FRS levels in a stepwise multiple regression model. Our results provide some evidence that dietary intake in the higher CVD risk group was inferior to that in the lower risk group and that dietary fat intake and IL-6 were associated with FRS and MS in Korean men.